(untitled) - Darren Redfern (New York, 1996)
The book begins with a "Getting Started with Maple" tutorial that lays the groundwork for using Maple efficiently and effectively. The following 13 chapters cover the commands and structure for specific disciplines of computation. Each chapter is prefaced by a quick introductory tutorial providing simple explanations and examples. Entries for individual commands contain information on various aspects, including common parameter sequences, what type of output to expect. All Maple commands are described in a precise, concise, and consistent manner. Topics, which include calculus, linear algebra, number theory, programming, and more, are explained in this book
Keywords: maple v release 4 ( computer program languge )